Dengue in the elderly: a review. Issue 8 (3rd August 2017) - Lin, Ray Junhao; Lee, Tau Hong; Leo, Yee Sin
ABSTRACT: Introduction : Changing dengue epidemiological trends have resulted in a shift in the disease burden to the adult population. Older adults suffer from poorer outcomes as compared to their younger counterparts, making clinical management of this sub-population particularly challenging. Areas covered : We present a review of the current literature on the changing epidemiology of dengue in the elderly, the atypical features of the clinical disease in this population with emphasis on severe disease presentations and challenges in the current management strategies. Expert commentary : Dengue in the elderly is an increasingly important yet greatly understudied area. There is an urgent need to refine the current diagnostic criteria to improve diagnosis, classification of disease severity and identify individuals in this population who are likely to progress to severe disease. Management strategies in this population would have to be adjusted to account for the increased number of co-morbidities. The role of the available dengue vaccines in this group is uncertain, and more studies into their safety and efficacy are critically needed.